Improving arteriovenous fistula rate: Effect on hemodialysis quality. Issue 2 (28th October 2013) - Karkar, Ayman; Chaballout, Ahmed; Ibrahim, Maher Haj; Abdelrahman, Mohammed; Al Shubaili, Mona
Abstract Vascular access (VA) is the lifeline for patients with end‐stage renal disease on regular hemodialysis (HD). Tunneled catheters have been associated with increased risk of luminal thrombosis, infection, hospitalization, and high cost. Our aims were to follow the "Fistula First Initiative, " avoid or reduce the rate of catheter insertion, improve the rate of arteriovenous fistula (AVF) use, and study the effect of increased AVF use on quality of dialysis and patient's outcome. A VA program has been established in collaboration with an enthusiastic and professional vascular surgery team to manage 358 patients who have been on regular HD treatment for a period ranging from 1 to 252 months. The mean ± standard deviation age of patients was 52 ± 15 years with 62% male patients. Over a period of 2 years, 408 procedures were performed. These include 293 AVFs and 56 arteriovenous grafts (AVGs). Other procedures include 39 permanent catheter insertions, 8 AVF aneurysmectomy, removal of 6 AVGs, embolectomy of 4 AVGs, excision of 1 AVG lymphocele, and ligation of 1 AVF. This program resulted in significant increase in AVF rate from 35% to 82%; reduction in catheter rate from 62% to 10.9%; infection rate down from 6.6% to 0.6%; VA clotting down from 5.1% to 1.0%; and increase in average blood flow rate from 214 ± 32 to 298 ± 37 mL/min (P < 0.01). These results have been associated with improved average single pool Kt/V from 0.88 ± 0.19 to 1.28 ± 0.2 (P < 0.01); increased hemoglobin from 9.2 ± 1.2 to 10.9 ± 0.9 g/dL (P < 0.01); improved serum albumin from 3.2 ± 0.5 to 3.7 ± 0.4 g/dL (P < 0.05); reduction in administered erythropoietin dose by 19%; and significant drop in hospitalization rate from 6.1% to 3.8%. These results confirm the great benefits of AVF on quality of HD and patient outcome, and clearly affirm that AVF should always be considered first.